Aquaporin 4‐Dependent expression of glial fibrillary acidic protein and tenascin‐C in activated astrocytes in stab wound mouse brain and in primary culture. Issue 1 (1st September 2014) - Ikeshima‐Kataoka, Hiroko; Abe, Yoichiro; Yasui, Masato
<x xml:space="preserve">Abstract</x> We previously reported that aquaporin 4 (AQP4) has a neuroimmunological function via astrocytes and microglial cells involving osteopontin. AQP4 is a water channel localized in the endofoot of astrocytes in the brain, and its expression is upregulated after a stab wound to the mouse brain or the injection of methylmercury in common marmosets. In this study, the correlation between the expression of AQP4 and the expression of glial fibrillary acidic protein (GFAP) or tenascin‐C (TN‐C) in reactive astrocytes was examined in primary cultures and brain tissues of AQP4‐deficient mice (AQP4/KO). In the absence of a stab wound to the brain or of any stimulation of the cells, the expressions of both GFAP and TN‐C were lower in astrocytes from AQP4/KO mice than in those from wild‐type (WT) mice. High levels of GFAP and TN‐C expression were observed in activated astrocytes after a stab wound to the brain in WT mice; however, the expressions of GFAP and TN‐C were insignificant in AQP4/KO mice. Furthermore, lipopolysaccharide (LPS) stimulation activated primary culture of astrocytes and upregulated GFAP and TN‐C expression in cells from WT mice, whereas the expressions of GFAP and TN‐C were slightly upregulated in cells from AQP4/KO mice. Moreover, the stimulation of primary culture of astrocytes with LPS also upregulated inflammatory cytokines in cells from WT mice, whereas modest increases were observed in cells from AQP4/KO mice. These results suggest that AQP4 expression accelerates GFAP and TN‐C expression in activated astrocytes induced by a stab wound in the mouse brain and LPS‐stimulated primary culture of astrocytes. © 2014 Wiley Periodicals, Inc.